Pengaruh Edukasi Melalui Media Whats App dan Leaflet Terhadap Perubahan Perilaku Berisiko Pada Siswa - Irnawati, Irnawati; Suriah, Suriah; Yusriani, Yusriani (Window of Health : Jurnal Kesehatan, 2019)
Adolescents are very susceptible to health risk behaviors such as smoking and drinking so they must be equipped with knowledge to prevent these risky behaviors early. This study aims to assess the effect of education through media media Whats App and leaflets on changes in risk behavior in Muhammadiyah Bungoro and the Pangkajene DDI Pangkep Regency. This study uses quasi-experimental experiments with pretest-posttest only control group design. The population in this study were grade 2 students enrolled in Muhammadiyah Bungoro and Pangkajen DDI Senior High Schools in Pangkep Regency as many as 330 students. The sample in this study were grade 2 students from the SMKS Muhammadiyah Bungoro and Pangkajene DDI High School in Pangkep Regency as many as 180 students. Sampling by purposive sampling. Data collection uses questionnaires given during pre-test and post-test. Processing data using the SPSS program. The results showed that before the education, knowledge and attitudes of students were more or less lacking, after giving education the students' knowledge and attitudes increased to be good. Increased knowledge was higher for students who received education through leaflets, while increasing attitudes were higher for students who received education via Whats App. This study concluded that there was an effect of education through leaflets and Whats App on changes in risky behavior of students (p <0.05).